Co-Pyrolysis of Cotton Stalks and Low-Density Polyethylene to Synthesize Biochar and Its Application in Pb(II) Removal - Xiaowei Yuan; Xuejun Zhang; Huijie Lv; Yonggang Xu; Tianxia Bai (Molecules, 2022)
It is inevitable that reclaimed cotton stalks will contain a certain amount of plastic film due to the wide application of plastic mulching during the process of cotton cultivation, and this makes it inappropriate to return it to the field or for it to be processed into silage. In this study, biochars were prepared by the co-pyrolysis of cotton stalk with low-density polyethylene (LDPE) in the proportions of 1:0, 3:1, 2:1, and 1:1 (w/w) at 400 °C, 450 °C, and 500 °C and maintaining them for 1 h. The effects of the co-pyrolysis of cotton stalk with LDPE on the properties of biochars (e.g., pH, yield, elemental analysis, specific surface area, etc.) and the Pb(II) removal capacity were analyzed. Co-pyrolysis cotton stalks with LDPE could delay the decomposition of LDPE but could promote the decomposition of cotton stalk. At 400 °C and 450 °C, the addition of LDPE decreased the H/C ratio, while no significant difference was found between the pristine biochar and the blended biochar pyrolyzed at 500 °C. An FTIR analysis indicated that the surface functional groups of biochar were not affected by the addition of LDPE, except for CH3 and CH2. The results of the SEM showed that LDPE could cover the surface of biochar when pyrolyzed at 400 °C, while many macropores were found in the blended biochar that was pyrolyzed at 450 °C and 500 °C, thus increasing its surface area. The blended biochar that was pyrolyzed at 500 °C was more effective in the removal of Pb(II) than the cotton-stalk-derived biochar, which was dominated by monolayer adsorption with a maximum adsorption capacity of approximately 200 mg·g−1. These results suggested that the co-pyrolysis of cotton stalks and LDPE may be used to produce biochar, which is a cost-effective adsorbent for heavy metal removal from aqueous solutions.